KALIMAT IMPERATIF DALAM FILM THE GREAT GATSBY (SUATU ANALISIS SINTAKSIS) - Worotikan, Felisa (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT This research attempts to identify, describe and analyze imperative sentences in the film â€™The Great Gatsbyâ€ directed by Baz Luhrmann. The data are taken from the film, â€œThe Great Gatsbyâ€ directed by Baz Luhrmann. The identified data are analyzed according to the concept of Aarts and Aarts on form and function of imperative sentences in communication. In analyzing the data, the writer uses descriptive method. The problems of this research focus on the forms and functions of imperative sentence found in the film â€œThe Great Gatsbyâ€. The results of this research show that the function of these entire imperative sentences found in the film are command, wish, invitation, and warning. The writer also finds the function of hope. Command is the most used function in the film. Key words : Imperative Sentences, Syntactic Analysis, Film â€œThe Great Gatsbyâ€